Experimental investigation of the dynamic behaviour of a fully passive flapping foil hydrokinetic turbine. (July 2019) - Duarte, Leandro; Dellinger, Nicolas; Dellinger, Guilhem; Ghenaim, Abdellah; Terfous, Abdelali
Abstract: The dynamic behaviour of a fully passive flapping foil hydrokinetic turbine is experimentally investigated at a Reynolds number of 6 × 10 4 . Previous numerical simulations showed that, depending on the location of the pitching axis l θ and the rotational stiffness k θ, four different responses may emerge from the system. Only one of them is suitable for energy harvesting purposes, which is characterised by large amplitude pitching and heaving oscillations about the equilibrium position. The present work experimentally validates these findings. A nondimensionalised chart delimiting the boundaries between the different responses in the parameter space l θ × k θ is provided, relying upon an original quantitative classifying map. It has been found that the pitching axis must be placed at least 29% of the chord length behind the leading edge in order for the foil to present a non stationary response. The ideal behaviour for harvesting purposes can be achieved without any pitching stiffness for a pitching axis location from 31% to 39% of the chord length, some pitching stiffness being needed for values above that range. Finally, sensitivity tests revealed a slight dependence of the transition boundaries on the heaving mass m y and stiffness k y, suggesting that an increase in the heaving natural frequency of the baseline prototype may help the system respond in the desired way for an energy extraction scenario.